El paradigma de la justicia restaurativa: Manifestacion de misericordia en el derecho penal de la Iglesia - Riondino, Michele (Vergentis, 2020)
To link mercy to ecclesial experience regarding sanctions would seem superfluous, except for those who attribute merely punitive objectives to penal systems (including the canonical system). Among the reasons that support this approach are some which claim to be derived from biblical tradition. It is true that training in the penal law of the Church is linked to her commitment to counteracting evil in the life of individuals and of the community. However, the connection between sanctions and penitential discipline is equally undeniable, clearly focused on the proclamation of mercy and the granting of forgiveness, especially in order for the Christian faithful to be able to participate worthily in the Eucharist, developing Paul's teaching in the First Letter to the Corinthians (11, 27).